2005
DOI: 10.1098/rsta.2005.1622
|View full text |Cite
|
Sign up to set email alerts
|

Computational steering in Monte Carlo simulations of thin film polystyrene

Abstract: High molecular weight polymer systems show very long relaxation times, of the order of milliseconds or more. This time-scale proves practically inaccessible for atomic-scale dynamical simulation such as molecular dynamics. Even with a Monte Carlo (MC) simulation, the generation of statistically independent configurations is non-trivial. Many moves have been proposed to enhance the efficiency of MC simulation of polymers. Each is described by a proposal density Q(x'; x): the probability of selecting the trial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The experimental data, 14,15 measured close to the T g and computational 28 findings, obtained at 500 K, show that the rings have a specific orientation at the surface: the angle the phenyl rings form with respect to the normal to the polystyrene (the definition is shown in Fig. 11) is approximately 57 .…”
Section: Atomistic Simulationssupporting
confidence: 62%
See 2 more Smart Citations
“…The experimental data, 14,15 measured close to the T g and computational 28 findings, obtained at 500 K, show that the rings have a specific orientation at the surface: the angle the phenyl rings form with respect to the normal to the polystyrene (the definition is shown in Fig. 11) is approximately 57 .…”
Section: Atomistic Simulationssupporting
confidence: 62%
“…In the last years both experimental studies 9,13-17 and computational studies 26,28 have been performed to investigate the structure of polymer surfaces at an atomistic level. The characteristics of a surface can influence the performance of the devices to which they belong and a knowledge of the superficial properties and how these properties change in the presence of different media 9,13,16,17 can help the engineering of the devices.…”
Section: Atomistic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of writing, more than ten codes, from within and outside the RealityGrid project, have been made steerable in this way and the steering system has been adopted by other projects, including the EPSRC's Integrative Biology. 3 There are several papers in the issue which describe steering and its wide-ranging scientific applications (for example, Kenny et al 2005;Mason & Sutton 2005). Other steering systems exist and Eickermann et al (2005) describe one of these.…”
mentioning
confidence: 99%
“…For supported PS films, the critical thickness is about 100 nm and it is independent of the substrate . Furthermore, the theoretical calculations Mason and Sutton (2005) and experiments (Gautam et al, 2000) on polystyrene showed that at both interfaces the preferred orientation of aromatic rings are out of the interface plane, at the film/substrate interface though, the tilt angle is higher than at the free surface.…”
Section: Mechanical Spectra Of Thin Polymer Filmsmentioning
confidence: 95%